2022
DOI: 10.3389/fendo.2022.956277
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid receptors in the endocrine regulation of glucose metabolism: Insight from gastrointestinal-pancreatic-adipose interactions

Abstract: Glucose metabolism is primarily controlled by pancreatic hormones, with the coordinated assistance of the hormones from gastrointestine and adipose tissue. Studies have unfolded a sophisticated hormonal gastrointestinal-pancreatic-adipose interaction network, which essentially maintains glucose homeostasis in response to the changes in substrates and nutrients. Free fatty acids (FFAs) are the important substrates that are involved in glucose metabolism. FFAs are able to activate the G-protein coupled membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 155 publications
0
6
0
Order By: Relevance
“…KEGG pathways analysis (Figure 4) also revealed many genes contributing to fat digestion and absorption pathways. Free fatty acids (FFAs) in particular have complex actions in the pancreas, but nevertheless are important regulators in glucose metabolism and insulin release, and the activation of their receptors directly impacts pancreas secretion [27]. They can also stimulate the release of CCK from enteroendocrine cells, which in turn induces pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KEGG pathways analysis (Figure 4) also revealed many genes contributing to fat digestion and absorption pathways. Free fatty acids (FFAs) in particular have complex actions in the pancreas, but nevertheless are important regulators in glucose metabolism and insulin release, and the activation of their receptors directly impacts pancreas secretion [27]. They can also stimulate the release of CCK from enteroendocrine cells, which in turn induces pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 99%
“…They can also stimulate the release of CCK from enteroendocrine cells, which in turn induces pancreatic enzyme secretion. While short-term exposure to FFAs, specifically long-chain fatty acids, results in insulin release from β-cells, it has been well documented that chronic exposure and/or lipotoxicity results in desensitization, impaired GSIS, insulin resistance, and, over the long-term, β-cell damage [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…73 Under low glucose concentrations, FFAs are converted to long-chain fatty acid coenzyme A (LC-CoA) by long-chain acyl-CoA synthetase and enter the mitochondria where they undergo β-oxidation to generate energy, 74 thus, the hypoglycemia is prevented. 7577 However, in one study it has been demonstrated that FFA induced insulin secretion independent on the oxidation of the fuel 78 and/or presence of glucose. 76 In contrast, excess consumption of dietary fats and oils has a negative impact on β-cells.…”
Section: Risk Factors For β-Cell Dysfunction In Type 2 Diabetesmentioning
confidence: 99%
“…Ingestible fats consist mainly of long-chain triglycerides (LCTs); overaccumulation of LCTs leads to hepatic steatosis and insulin resistance, both of which are closely linked to cardiovascular disease, cancer, and death (3)(4)(5). To prevent the onset and exacerbation of such lifestyle-related diseases, receptors and hormones involved in digestion, absorption, and accumulation of LCTs have drawn much attention recently (6,7).…”
Section: Introductionmentioning
confidence: 99%